Cold field electron emission of large-area arrays of SiC nanowires: photo-enhancement and saturation effects. Issue 35 (17th August 2016) - Carapezzi, Stefania; Castaldini, Antonio; Fabbri, Filippo; Rossi, Francesca; Negri, Marco; Salviati, Giancarlo; Cavallini, Anna
Abstract : Photo-enhanced field emission from SiC nanowires showed the presence of a saturation region, which is of interest for nanotechnological applications. Abstract : This paper explores the cold field emission (CFE) properties of SiC nanowire (NW) arrays. The CFE currents were studied in the dark and under ultra-violet (UV) irradiation conditions. An increase in CFE current was observed when the SiC NW arrays were illuminated, with a consequent decrease in the values of the turn-on field and the threshold field. Furthermore, while dark CFE currents were well described by the standard Fowler–Nordheim (FN) theory for metals, the photo-enhanced CFE currents showed nonlinearity in FN plots. Specifically, a voltage range of current saturation appeared, which is appealing for nanotechnological applications, and it is indeed an essential prerequisite for realizing devices such as FE photocathodes.